Cytological features of hepatoid adenocarcinoma of the gallbladder: A case report with immunocytochemical analyzes. Issue 8 (10th April 2018) - Yoshioka, Saya; Ishida, Mitsuaki; Okano, Kimiaki; Sandoh, Kaori; Ebisu, Yusuke; Miyasaka, Chika; Yamamoto, Tomohisa; Ryota, Hironori; Satoi, Sohei; Tsuta, Koji
Abstract : Hepatoid adenocarcinoma is defined as an extrahepatic malignant neoplasm showing morphological and immunohistochemical resemblance of hepatocellular carcinoma. The occurrence of this type of tumor in the gallbladder is extremely rare. In this study, we report the first cytological case of hepatoid adenocarcinoma of the gallbladder. An 80‐year‐old Japanese female was found to have a tumorous lesion in the gallbladder. Papanicolaou smear of the ascites demonstrated a few epithelial cell clusters composed of round to oval neoplastic cells with distinct cell border and large centrally‐located nuclei. Tumor touch smear of the resected tumor revealed the presence of two distinct neoplastic components. The first component was composed of clusters or sheets of epithelial cells with distinct cell border, relatively rich clear cytoplasm, and centrally‐located nuclei, as seen in the ascites specimen. The other component was composed of tall columnar cells with large basally‐oriented nuclei, and glandular formation was noted as well. Immunocytochemical analyzes of the touch smear material demonstrated that the former component was positive for HepPar1, thus it was considered as a hepatoid adenocarcinoma, and the latter component deemed as a typical adenocarcinoma. Histopathological and immunohistochemical examination of the resected gallbladder tumor confirmed a diagnosis of hepatoid adenocarcinoma. The characteristic cytological features of hepatoid adenocarcinoma are the presence of sheets or clusters of neoplastic cells with distinct cell border and centrally‐located nuclei. Immunocytochemical analysis for HepPar1 may help its diagnosis. Demonstration of hepatoid adenocarcinoma is important in the cytological specimen because this type of tumor shows an aggressive clinical course.